2023
DOI: 10.3390/nu15092170
|View full text |Cite
|
Sign up to set email alerts
|

Adansonia digitata L. (Baobab) Bioactive Compounds, Biological Activities, and the Potential Effect on Glycemia: A Narrative Review

Abstract: Adansonia digitata L. fruit, also known as baobab, has been used traditionally throughout the world for its medicinal properties. Ethnopharmacological uses of various plant parts have been reported for hydration, antipyretic, antiparasitic, antitussive, and sudorific properties and also in the treatment of diarrhea and dysentery in many African countries. Several studies have revealed that in addition to these applications, baobab has antioxidant, anti-inflammatory, analgesic, and antimicrobial activities. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…A variety of tannins derived from medicinal plants help to slow the onset of diabetes and its associated complications by acting on key biochemical pathways and targets 75 . It has been demonstrated that tannins minimize the risk of developing diabetes by improving glucose absorption and lowering blood sugar levels 76 . Saponins enhance the activities of various antioxidant enzymes such as catalases and superoxide dismutase, which is usually lowered in hyperglycemic conditions 77 …”
Section: Discussionmentioning
confidence: 99%
“…A variety of tannins derived from medicinal plants help to slow the onset of diabetes and its associated complications by acting on key biochemical pathways and targets 75 . It has been demonstrated that tannins minimize the risk of developing diabetes by improving glucose absorption and lowering blood sugar levels 76 . Saponins enhance the activities of various antioxidant enzymes such as catalases and superoxide dismutase, which is usually lowered in hyperglycemic conditions 77 …”
Section: Discussionmentioning
confidence: 99%
“…In this unit, AAE means ascorbic acid equivalents and DW means dried weight. Mohammed [ 20 ] studied the chemical composition of Adansonia digitata L. fruit pulp, which is important because of its medicinal values [ 21 ]. A total of 18 phenolics and flavonoids were isolated, and the DPPH of leaf MeOH extracts demonstrated the potential of A. digitata leaves as a promising source of natural antioxidant compounds.…”
Section: Antibacterial and Antioxidant Properties Of Natural Extractsmentioning
confidence: 99%
“…It is widely recognized for its socioeconomic significance for the local populations due to the plant's many useful organs, which can be used for food, or for traditional medicine [1]. The Adansonia genus, a member of the Malvaceae family, encompasses eight identified species spread across numerous African countries [2]. Besides their nutritional importance, the protection of these wild fruits not only contributes to health but also yields economic advantages, as certain wild edible fruits are actively traded in various markets.…”
Section: Introductionmentioning
confidence: 99%